Advancing Multicultural Education in Indonesia: Insights from Amin Abdullah’s Perspective - Mawi Khusni Albar; Sangkot Sirait; Mahmud Arif; Nur Lailatun Furoidah; Satria Adi Pradana (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This article examines multicultural education through the lens of Amin Abdullah, a notable Indonesian Muslim scholar. Using a descriptive-qualitative approach, it reviews his works to elucidate his perspective. Abdullah’s ideas address Indonesia’s diverse social and cultural landscape, emphasizing intercultural understanding and tolerance, particularly in the post-Suharto era, marked by the resurgence of ethnic and religious identities. The article defines multicultural education and its goals, explores the influence of organizations like Muhammadiyah and Nahdlatul Ulama on Abdullah’s thought, and discusses the implications for Indonesian education. It advocates for inclusive curricula, tolerance promotion, teacher training, and multicultural materials, while addressing challenges such as resistance from conservative groups. Integrating perspectives from other scholars, it offers a comparative analysis within the broader discourse on multicultural education, enhancing understanding of integrating cultural and religious diversity into Indonesian education, while noting potential limitations and practical application difficulties